2021
DOI: 10.1242/dev.199386
|View full text |Cite
|
Sign up to set email alerts
|

Ret signaling in ureteric bud epithelial cells controls cell movements, cell clustering and bud formation

Abstract: Ret signaling promotes branching morphogenesis during kidney development, but the underlying cellular mechanisms remain unclear. While Ret-expressing progenitor cells proliferate at the ureteric bud tips, some of these cells exit the tips to generate the elongating collecting ducts, and in the process turn off Ret. Genetic ablation of Ret in tip cells promotes their exit, suggesting that Ret is required for cell rearrangements that maintain the tip compartments. Here, we examine the behaviors of ureteric bud c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…100 This may be important for epithelial cell proliferation and motility reported in the UB tips. 41,42,57,[101][102][103][104] Thus, the identified changes together with existing data propose a proliferation-and stretching-based model for driving new branch formation in the developing kidney. More specifically, our results suggest that to reach an ampulla stage, cells unevenly increase in volume, partially due to high proliferation, 15 which triggers crowding at the ampulla stage.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…100 This may be important for epithelial cell proliferation and motility reported in the UB tips. 41,42,57,[101][102][103][104] Thus, the identified changes together with existing data propose a proliferation-and stretching-based model for driving new branch formation in the developing kidney. More specifically, our results suggest that to reach an ampulla stage, cells unevenly increase in volume, partially due to high proliferation, 15 which triggers crowding at the ampulla stage.…”
Section: Discussionmentioning
confidence: 85%
“…Interestingly, previous study reports that epithelial cells round up when their adherens junctions are disrupted ( 89 ). This may be important for epithelial cell proliferation and motility reported in the UB tips ( 41, 42, 44, 9093 ). Thus, the identified changes together with existing data propose a proliferation- and stretching-based model for driving new branch formation in the developing kidney.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Genetic mosaic experiments revealed that the expression level of Ret in a given cell is associated with the position that cell adopts within the developing ureteric tree. Cells lacking Ret are excluded from branch tips and populate branch stalks [56], whereas cells with constitutively high Ret remain in branch tips [57]. However, it is not immediately obvious how this cell sorting contributes to branching morphogenesis.…”
Section: Cell Sortingmentioning
confidence: 99%
“…In mesenchymefree explants, epithelial branches form in a random pattern that does not resemble the orderly bifurcations observed in vivo or in whole-organ explants. In genetic mosaic experiments using explants, cells with constitutive expression of Ret come together and initiate branches [57], suggesting that high Ret activity promotes a form of epithelial-intrinsic branching, albeit one with currently unknown cellular mechanisms. Sorting of cells with different levels of Ret signaling in vivo might help to restrict this 'branchinitiating activity' to branch tips.…”
Section: Cell Sortingmentioning
confidence: 99%